HOMAGE / Museum of rural life in Gothenburg - Mattisson, Klara (My University, 2020)
From growing up in the countryside, I have always felt fascination towards old barns and byres, located like singular figures in the open landscape. With their honest materiality, robust heterogeneity and careful response to setting, these structures represents an elemental architecture that seem to never pass from time. After reading Ur den svenska byggnadskonstens magasin, a book released 30 years ago, where architect Bengt Lindroos declare his enchantment towards aforementioned typologies, I got inspired to create my own obeisance. Homage is a project that seeks to tribute rural life in contemporary built form. Through tactile, tectonic and telluric qualities create spaces that bonds to both culture and content. With emphasis put on the local history of agricultural properties in the city of Gothenburg, the aim of this master’s thesis is to form a public building through interpretations of the traditional Swedish barn and byre. The predicted outcome is a museum of rural life, that collects, archives and displays the memory of a significant past influencing the present. Not least with the building itself as an exhibitional piece.
Keywords: rural life, vernacular, interpretation, landeri, museum